How to Improve Bayberry (Myrica rubra Sieb. et Zucc.) Juice Flavour Quality: Effect of Juice Processing and Storage on Volatile Compounds - Xu, Yi; Zhang, Min; Fang, Zhongxiang; Sun, Jin; Wang, Ying (Elsevier, 2014)
To improve the flavour quality of bayberry juice, effects of different raw materials, heat treatment and storage time on the flavour variations were investigated. Changes of total sugar and titratable acids were also monitored. Identification and quantitation of volatile flavour compounds were performed by headspace solid-phase microextraction couped with gas chromatography–mass spectrometry (HS-SPME–GC–MS). The contents of esters, alcohols, total sugar and titratable acidity of the rancid flavour raw juice were 6.03%, 8.24%, 5.56 g/L, 0.18 g/L less than those of pleasing flavour raw juice (PF), while the content of aldehydes was 4.19% higher than that of PF. After 9 months storage, the bayberry juice produced fermentation-like flavours with alcohols increases (11.45%) while esters (14.91%) and total sugar (3.27 g/L) decreases. The results suggested that proper juice processing and storage techniques are critical to the flavour quality of bayberry juice.